Infant feeding: beyond the nutritional aspects - Giselia A.P. Silva; Karla A.O. Costa; Elsa R.J. Giugliani (Elsevier, 2016)
Objective: To draw attention to the importance of interaction between caregiver and child during feeding and the influence of parenting style on dietary habit formation. Source of data: A search was performed in the PubMed and Scopus databases for articles addressing responsive feeding; the articles considered most relevant by the authors were selected. Synthesis of data: The way children are fed is decisive for the formation of their eating habits, especially the strategies that parents/caregivers use to stimulate feeding. In this context, responsive feeding has been emphasized, with the key principles: feed the infant directly and assist older children when they already eat on their own; feed them slowly and patiently, and encourage children to eat but do not force them; if the child refuses many types of foods, experiment with different food combinations, tastes, textures, and methods of encouragement; minimize distractions during meals; and make the meals an opportunity for learning and love, talking to the child during feeding and maintaining eye contact. It is the caregiver's responsibility to be sensitive to the child's signs and alleviate tensions during feeding, and make feeding time pleasurable; whereas it is the child's role to clearly express signs of hunger and satiety and be receptive to the caregiver. Conclusion: Responsive feeding is very important in dietary habit formation and should be encouraged by health professionals in their advice to families. Resumo: Objetivo: Chamar a atenção para a importância da interação entre cuidador e criança durante a alimentação e a influência do estilo de parentalidade na formação do hábito alimentar. Fontes dos dados: Foi realizada busca na base de dados PubMed e Scopus de artigos abordando a alimentação responsiva, tendo sido selecionados aqueles julgados mais relevantes pelos autores. Síntese dos dados: O modo de alimentar as crianças é decisivo na formação do hábito alimentar, sobretudo as estratégias que os pais/cuidadores utilizam para estimular a alimentação. Nesse contexto, a alimentação responsiva tem merecido destaque, tendo como princípios-chave: alimentar a criança pequena diretamente e assistir as mais velhas quando elas já comem sozinhas; alimentar lenta e pacientemente, e encorajar a criança a comer, mas não forçá-la; se a criança recusar muitos alimentos, experimentar diferentes combinações de alimentos, de gostos, texturas e métodos de encorajamento; minimizar distrações durante as refeições; e fazer das refeições oportunidades de aprendizado e amor, falando com a criança durante a alimentação e mantendo contato olho a olho. Cabe ao cuidador a responsabilidade de ser sensível aos sinais da criança e aliviar tensões durante a alimentação, além de torná-la prazerosa; enquanto é papel da criança expressar os sinais de fome e saciedade com clareza e ser receptiva ao cuidador. Conclusão: A alimentação responsiva é muito importante na formação dos hábitos alimentares e deve ser incentivada pelos profissionais de saúde, orientando as famílias como praticá-la. Keywords: Responsive feeding, Parental feedings practices, Parenting styles, Infant feeding, Palavras-chave: Alimentação responsiva, Práticas alimentares parentais, Estilos parentais, Alimentação infantil